Building a K-community through the K-economy - Anuar, Abdul Rahim; Jamaludin, Zulikha (2005)
This paper focuses on the strategy that has been drawn by the Knowledge-based Economic Plan for fortifying the development of the country’s K-economy. With the strength of the electronic industry cluster since the late 1980s, where a large portion was generated by American, Japanese, and Taiwanese multi-national companies, Information and Communication Technology (ICT) linked with the electronic industry was developed through the Multimedia Super Corridor programme (MSC). MSC was made the catalyst and was the base for the development of the ICT industry. Through the MSC and the process of linked development, the long term economic growth will by driven by knowledge and technology. In the Ninth Malaysian Plan (2006-2010), better known as the RMK-9, much effort is being and will be taken by the government in preparing a more secure platform to enable the country to easily shift toward K-economy and K-Malaysia. Since ICT happens to be a main factor in the process of K-economic development and a K-Malaysia, efforts have been and will be increased by the government to streamline the access to ICT services and facilities that is more encompassing in all aspects of daily life. The development of human capital toward K-labour is also a critical aspect under the RMK-9 for bridging the digital divide through access to ICT services and facilities. Therefore, ICT training programmes and education is currently and will be augmented and broadened to schools, pre-universities, and institutions of higher education. Overall, the pathway for K-economic development of the country is still at the early stages of development. There exists dualism in the development of the country’s K-economy from the aspects of infrastructure and infostructure. The development of infrastructure is more advanced that the development of infostructure. There exists a digital divide between the rich and poor, and the urban and rural residential areas. This illustrates that the journey toward achieving the levels of advancement experienced by the developed countries is still very long, especially with the targeted levels the of information community, K-economy and K-Malaysia that have been identified.